Overdose Experiences among People Who Inject Drugs in West Virginia: Personal Loss, Psychological Distress, Naloxone, and Fentanyl. (2nd January 2023) - Schneider, Kristin E.; Allen, Sean T.; Winiker, Abigail K.; White, Rebecca Hamilton; O'Rourke, Allison; Sherman, Susan G.; Grieb, Suzanne M.
Abstract: Background: As overdose remains a major public health concern in the United States, it is important to understand the experiences people who inject drugs (PWID) have with overdose. Past experiences during such emergencies are an important determinant of future behavior, including help seeking, which can be lifesaving. Methods: We explored experiences with overdose, using data from 21 in-depth interviews collected from PWID in a rural county in West Virginia (Cabell County). We used an iterative, modified constant comparison approach to synthesize resulting interview data. Results : Participants reported pervasive experiences with overdose, including through their own personal overdose experiences, witnessing others overdose, and losing loved ones to overdose fatalities. Experiencing emotional distress when witnessing an overdose was common among our participants. Many participants reported regularly carrying naloxone and using it to reverse overdoses. Multiple participants described believing the myth that people grow immune to naloxone over time. Concerns about the presence of fentanyl in drugs were also common, with many participants attributing their own and others' overdoses to fentanyl. Conclusions : Our findings have important implications for naloxone access and education, as well as policies and practices to encourage help seeking during overdose events among rural PWID. Participant concerns about fentanyl in the drug supply highlight the need for access to drug checking technologies.